Aneurysm characteristics and risk of rebleeding after subarachnoid haemorrhage. (June 2019) - Koopman, Inez; Greving, Jacoba P; van der Schaaf, Irene C; van der Zwan, Albert; Rinkel, Gabriel JE; Vergouwen, Mervyn DI
Introduction: Knowledge of risk factors for rebleeding after aneurysmal subarachnoid haemorrhage can help tailoring ultra-early aneurysm treatment. Previous studies have identified aneurysm size and various patient-related risk factors for early (≤24 h) rebleeding, but it remains unknown if aneurysm configuration is also a risk factor. We investigated whether irregular shape, aspect- and bottleneck ratio of the aneurysm are independent risk factors for early rebleeding after aneurysmal subarachnoid haemorrhage. Patients and methods: From a prospectively collected institutional database, we investigated data from consecutive aneurysmal subarachnoid haemorrhage patients who were admitted ≤24 h after onset between December 2009 and January 2015. The admission computed tomographic angiogram was used to assess aneurysm size and configuration. With Cox regression, we calculated stepwise-adjusted hazard ratios (HRs) with 95% confidence intervals (CIs) for irregular shape, aspect ratio ≥1.6 mm and bottleneck ratio ≥1.6 mm. Results: Of 409 included patients, 34 (8%) patients had in-hospital rebleeding ≤24 h after ictus. Irregular shape was an independent risk factor for rebleeding (HR: 3.9, 95% CI: 1.3–11.3) after adjustment for age, sex, PAASH score, aneurysm location, aneurysm size and aspect- and bottleneck ratio. Aspect ratio ≥1.6 mm (HR: 2.3, 95% CI: 0.8–6.5) and bottleneck ratio ≥1.6 mm (HR: 1.7, 95% CI: 0.8–3.6) were associated with an increased risk of rebleeding, but were not independent risk factors after multivariable adjustment. Conclusions: Irregular shape is an independent risk factor for early rebleeding. However, since the majority of subarachnoid haemorrhage patients have an irregular aneurysm, additional risk factors have to be found for aneurysm treatment prioritisation.